Association between physical activity and cardiovascular parameters in 7-year-old children: a Chinese cross-sectional study - Qianchuo Wang; Hualin Wang; Bowen Du; Yujian Wu; Zhuoyan Li; Yiwei Niu; Fengxiu Ouyang; Kai Bai; Jian Wang; Kun Sun (BMC, 2024)
Abstract Introduction Physical activity (PA) is believed to play an important part in many aspects during childhood and adolescence, especially cardiorespiratory fitness and cardiometabolic health. However, whether different levels of PA in daily life influence the structure or function of heart in school-aged children remains unknown. We aimed to investigate the association between PA and cardiovascular parameters in 7-year-old children. Methods Follow-up data from the Shanghai Prenatal Cohort Study and the Shanghai Birth Cohort was analyzed. Perinatal information including both maternal and offspring datum was recorded. A refined questionnaire was used to evaluate the frequency and duration of children's PA levels. Blood pressure, echocardiography, and anthropometry assessment were conducted during the follow-up of 7-year-old children. Results Overall, high PA level was associated with higher left ventricle posterior wall thickness in diastole (LVPWd, β coefficient: 0.36, 95% CI: 0.12, 0.61), higher left ventricle mass index (LVMI, β = 0.28, 95% CI: 0.07, 0.48), mitral E/a ratio (β = 0.47, 95% CI: 0.22, 0.71) and slower heart rate (β = -0.32, 95% CI: -0.57, -0.07), compared to low PA level. Medium PA level was associated with lower diastolic blood pressure (DBP, β = -0.18, 95% CI: -0.35, -0.01). In subgroup analysis, increased relative wall thickness (RWT) was found in high PA level boys (β = 0.36, 95% CI: 0.05, 0.67), and systolic blood pressure (SBP) showed a significant decrease in high PA level girls (β = -0.42, 95% CI: -0.78, -0.06). Conclusions This study suggested non-athlete children having higher PA level were associated with thicker left ventricle (LV) walls and better LV diastolic function, as well as slower heart rate and DBP at the age of 7. Furthermore, disparity in the association between PA level with morphological heart patterns and blood pressure existed in different sex category.